The Romanian Settlement Policy During the Period of State Socialism - Hajdú, Zoltán (Discussion Papers, 2022)
The theoretical, historical, political and practical problems of state socialism (state capitalism) had essentially been the personal matter of the Soviet Union up to the end of World War II. After the Central European communist changes, the issue of the state socialist system turned up as essential and common characteristics of each small socialist country. Besides essential similarities, each structure’s national characters could appear and develop. In the Romanian state socialist era (December 1947 – December 1989), regional and settlement (urban and rural) policy became an integral part of Romanian state socialism. The party and the state intervened into the regional and local processes according to the changing political considerations. One of the basic issues of the state socialist era is modernisation, including the acceleration of economic and social development. Romanian social, planned economic and settlement political processes were primarily influenced by the theoretical and practical political aspirations of Stalin and Krushchev, which were recapitulated under Nicolae Ceauşescu. Building settlement centres and increasing their urbanisation level were almost under continuous consideration. Privileged towns, especially Bucharest and county seats, were dominant in the era, but the foci of development changed from time to time. Romania’s population – due in part to hard-line population policy interventions – increased from 15.8 to 23.2 million people between 1948 and 1990, which in itself raised enormous economic, social, settlement developmental and housing issues. The transformation of the economic, social, political and administrational relations of villages was also a permanent element of Romanian state socialism, and rural policy did not begin with the physical and technical liquidation of villages. Settlement policy in Romania has in many ways become ripe for re-analysis. The Romanian state socialist period ended 20 years ago, and many of these previous processes can now be analysed from the historical perspective. This paper concentrates on the political and territorial–political correlation of development processes. The analyses of contents of different kind of official publications (minutes of party congresses, government decisions etc.) and texts of the laws in this issue are considered as important, though political improvisation had also gained considerable position in the substantial period of the era.